Farmers' Livelihood Security through Sheep Farming in Bareilly District of Uttar Pradesh - Verma, Harideep; Singh , Madan; Shruti,; Meena, H. R. (Indian Journal of Extension Education, 2025)
The study was conducted in 2024 to assess the livelihood security of sheep-owning farmers in Bareilly district, Uttar Pradesh. A Livelihood Security Index (LSI) was developed based on five key dimensions: food and nutritional security, economic and marketing security, infrastructural security, social security, and resource use efficiency. Content validity and relevance were tested using scoring methods. Data were collected from farmers using a structured interview schedule, and LSI was computed through standardized scoring and weighted aggregation. Correlation analysis using SPSS (SPSS 26.0) identified the relationship between livelihood security and selected socio-economic variables. Results revealed that most farmers had a moderate level of livelihood security (composite index = 0.617), with resource use efficiency and economic security being the strongest areas. Income, education, flock size, extension contact, and knowledge had significant positive correlations with livelihood security, while credit access showed a negative correlation. The study concluded that targeted interventions in infrastructure, financial literacy, and behavioural capacity-building are essential to enhance the livelihood resilience of smallholder sheep farmers.